Low Level of Associativity of the Panela Agroindustry: Case Study Santana, Colombia - Fino-Hernández, Fredy Fernando; Munevar-Romero, Melisa Daniela; Ulloa-Torres, Sergio (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper aims to describe the perception of the sociodemographic, productive and economic characteristics of the associativity of panela (“Panela” is a solid sugar made of sugarcane juice. Names other as jaggery or non-centrifugal cane sugars) producers in the municipality of Santana (Colombia) in 2022. An exploratory study was conducted, in which 50 members of five panela associations were interviewed about socio-demographic, productive and economic characteristics. It was found that most of the respondents have a secondary education; furthermore, they believe that the lack of training in solidarity economy and teamwork is a cause of the withdrawal of members. The majority of the respondents participate in the production and marketing of panela cane and believe that the purpose of the organizations should be the production and marketing of panela. They have between 5 and 10 ha of cane in production, harvest 2 to 4 times a year, and produce less than 12,000 kg of cane per week. The majority believes that a price below 3,000 Colombian pesos per kilogram of panela does not cover the production costs (2,500 to 3,500 COP). It is concluded that associativity is essential for the success of this agribusiness, but it is necessary to address the causes of withdrawal of members. Effective price and cost management is crucial to ensure the sustainability and growth of the sector. These findings provide valuable information for the design of policies and programs through associations.